Analisis Kesalahan Siswa Terkait Aspek Communication, Mathematising , Dan Representation Pada Unsur Proses Literasi Matematis Pisa - Elwan Stiadi; Fitriani Fitriani; Ari Putra (JTMT: Journal Tadris Matematika, 2023)
This study aims to analyze student errors related to the components of the PISA mathematical literacy process. This research is a qualitative descriptive study. In this study, the research subjects were students in grades IX 1 and IX 2 at SMP Negeri 4 Bengkulu City in the odd semester of the 2021/2022 academic year. Data collection techniques used in this study, namely test and interview methods. The components of the PISA mathematical literacy process discussed in this study are Communication, Mathematising, Representation.. The results showed that there are 40,85% of students make the error of communication processes. There are 48,59% of students make error of mathematising process. There are 53,41% of students make error of representation process.